Subsea controls future proofing: A systems strategy embracing obsolescence management - Abili, Nimi; Onwuzuluigbo, Raluchukwu; Kara, Fuat (Cranfield University, 2013)
The increasing world energy demands for enhanced oil and gas recovery in the offshore industry has led to new subsea technology developments with increased system functionality. Technologies such as subsea processing and instrumentations for subsea control data acquisition place a greater demand on bandwidth, power and capacity. Therefore, the legacy controls system becomes obsolete and proves unsustainable in supporting the increased functionality placed on it by the new subsea technologies. With the fast evolution of electronics, the replacement of the core components of the control system when they fail becomes difficult as they are no longer being produced or supported by the original component manufacturers (OCM). The present paper explores the different strategies in addressing obsolescence on the subsea controls system for offshore field developments.